Accuracy of tooth color determination by dental students using daylight-calibrated dental operatory lighting sources - Labis, Christos; Seceleanu, Irina; Rion, Kevin; Hassel, Alexander J.; Corcodel, Nicoleta (The journal of prosthetic dentistry, 2025)
Statement of problem - Lighting conditions are an essential factor for accurately determining tooth color. However, the ideal lighting conditions for determining tooth shade are rarely met and are difficult to quantify. While the use of a standardized daylight lamp D55 can improve accuracy, its high cost limits its use in dental offices. The use of modern operatory treatment units for tooth color determination is promising, as they now allow for the adjustment of light source settings such as color temperature and intensity. However, studies are needed to determine whether they provide accurate color determination. - Purpose - The purpose of this study was to assess the accuracy of visual tooth shade determinations under the adjusted light sources of 2 different dental treatment units in comparison with a standardized daylight lamp D55. - Material and methods - Dental treatment units from 2 manufacturers KaVoLUX 540 LED (LK) and LEDview Plus (LDS) were tested. The light sources of these units were adjusted to match daylight conditions. A daylight lamp (Dialite Color 7; Eickhorst & Co. KG) was used as a control (D55). A total of 49 participants (median age of 25 years, 30 women) underwent the Ishihara screening and received standardized training calibration. A total of 2205 clinical visual tooth shade determinations were performed with the Toothguide Training Box using the Vita 3D-Master shade guide under the 3 different lighting types. Each participant had 15 color determinations made under each of the 3 light settings. Color differences were analyzed by using the Kruskal-Wallis, Wilcoxon rank-sum, and chi-squared tests (α=.05). - Results - The type of lighting used for tooth shade determination had no significant effect on the accuracy of selected shade based on the ΔE00 metric (P=.133). Perfect matches were achieved in 50.8% of the cases under LK, 49.8% under LDS, and 53.6% under D55 light, with no significant difference among percentages (P=.315). Although there was a significant difference in time elapsed for shade determination by light type (P=.004), this difference was not clinically relevant (20.8 seconds for LK, 23.9 seconds for LDS, 21.9 seconds for D55). - Conclusions - The accuracy of color determination for both examined dental operatory lamps was found to be comparable with that of the standard D55 daylight lamp when adjusted to specific settings.